Pig olfaction: the potential impact and use of odors in commercial pig husbandry - Schild, Sarah-Lina Aagaard; Rørvang, Maria Vilain (Frontiers in Animal Science, 2023)
Pigs are widely acknowledged for their olfactory abilities. Regardless, research on pigs' olfactory capacities has focused mainly on aspects of olfaction which directly impact production, such as palatability of feed and pheromones to stimulate reproduction. Several basic research questions remain unanswered, such as: which odors do pigs like/dislike, and how may odors enrich their lives? This review aims to explore the currently available literature on pig olfaction to elucidate the current knowns and unknowns within the topics: Chemicals in the pig environment, olfactory organs of the pig, olfactory detection and acuity, behavioral reactions to odors, aversive odors, reaction to novel odors, attractive odors, and odors as a management tool in commercial pig production. The review focusses on complex odors of non-social origin (e.g., ammonia), and when information on this topic is lacking, we include information from research on other mammalian species. We found that the olfactory organs of pigs are functional already at birth and piglets can recognize the smell of the sow within 12h postpartum. Compared to humans, and several other mammalian species, the pig's olfactory system is highly developed, and the use of their sense of smell incorporated into their natural behavior. While sniffing is well-known behavior of pigs' exploratory behavioral repertoire, this review points to a lack of knowledge on pigs' behavioral reactions specifically when exposed to odors. Some odors appear attractive to pigs, whereas others appear repellent. Depending on the properties of the odor, providing pigs access to odors may be a way to stimulate their sense of smell, and could possibly be used in commercial pig production to enrich their lives. The review lastly highlight potential risks for animal welfare that the lacking knowledge poses, and propose future research questions and ways to utilize pigs' sense of smell in the daily management of the animals. Further research on the olfactory abilities of pigs could help ensure a more sustainable pig production.